A4. EGFL7 in placenta trophoblast and endothelial cells: implications in the pathogenesis of pre-eclampsia. (12th August 2016) - Massimiani, M.; Salvi, S.; Piccirilli, D.; Vecchione, L.; Moresi, S.; Ferrazzani, S.; Stuhlmann, H.; Campagnolo, L.
Abstract: Introduction : Placental development requires invasion and differentiation of trophoblast cells, together with coordinated fetal vasculogenesis and maternal vascular remodeling. During placental development, extravillous cytotrophoblasts invade the uterine spiral arteries of the decidua and myometrium. These invasive cytotrophoblasts replace the endothelial layer of the maternal spiral arteries, transforming them from high-resistance vessels into large-caliber capacitance vessels capable of adequately nourishing the fetus. These events are fine-tuned by a variety of factors critical for a successful pregnancy. Inadequate cytotrophoblast invasion and an incomplete uterine spiral artery remodeling may result in disorders of pregnancy, including intrauterine growth restriction, pre-term labor and preeclampsia (PE). Recent studies suggested that epidermal growth factor-like domain 7 (EGFL7) may play a role in this context. EGFL7, originally identified as an endothelial-restricted gene, is critical for embryonic vascular development. We recently demonstrated that EGFL7 in the placenta is expressed not only by endothelial cells of both the maternal and fetal vasculature, but also by the trophoblast cell lineage, throughout placental development. Previous studies showed that EGFL7 is able to interact with and modulate NOTCH signaling. Moreover, EGFL7 is able to activate EGFR, whose pathways play a major role in trophoblast migration. Methods : To investigate the role of EGFL7 in the trophoblast, we generated stable overexpression and downregulation of EGFL7 in both the human choriocarcinoma cell line Jeg3 and primary human trophoblast. The migration and invasion ability of these cells were tested using wounding and transwell assays. Protein extracts from serum starved EGFL7-overexpressing trophoblast cells were analyzed by western blot for EGFR, ERK and AKT phosphorylation. In addition, we evaluated if EGFL7 overexpression in trophoblast cells is associated to altered expression of the NOTCH signaling pathway using immunofluorescence and qRTPCR. By using inhibitors of both pathways, variations in migration/invasion ability induced by EGFL7 overexpression were investigated. Spatial distribution of EGFL7 was studied by immunofluorescence and qRT-PCR analyses in placental tissues of normal and preeclamptic pregnant women. Results : EGFL7 overexpression in Jeg3 and in primary trophoblast cells resulted in significantly increased cell migration and invasiveness, while its knockdown strongly reduced both phenomena. Analysis of EGFR, MAPK and PI3K pathways and the use of specific inhibitors in transwell assay showed that EGFL7 promoted trophoblast cell motility by activating these pathways. In addition, we demonstrated that EGFL7 triggered migration of trophoblast cells involved a concomitant activation of NOTCH signaling. Immunofluorescence analysis of placental tissues from preeclamptic ( n = 10) and normal pregnant women ( n = 10) showed lower levels of EGFL7 in both endothelial and trophoblast cells. This observation was quantified by qRT-PCR, which revealed that EGFL7 mRNA expression was significantly decreased by more than 10-fold in PE when compared to normal pregnancies. Conclusions : Our data suggest that EGFL7 regulates cell migration and invasion of trophoblast cells by activating MAPK, PI3K and NOTCH signaling pathways. These results suggest a correlation between EGFL7 reduced expression and the inadequate trophoblast invasion observed in PE.